Qualitative analysis on watermarking algorithm for large resolution camera phone image - Saquib, Nazmus; Gunawan, Teddy Surya; Olanrewaju, Rashidah Funke; Islam, Shayla; Hasan, Mohammad Kamrul (2014)
The Digital Water Marking (DWM) algorithm is used to serve security of image, audio and video data. Now days, it has been being used to keep the privacy and resist the intruders and piracy. Our mobile phone is a very important personal material for daily choir. We keep personal data and can pick photo and store it in our cell memory. Sometimes important personal photos could be copied or taken by others via blue tooth. To resist such kind of intruding it’s important to have a security system in those mobile phones. Beside that the robustness and strong security are also needed by using easy techniques. The aim of this paper is to analyze on a Robust Watermark Technique (RWT) which can be easier; more secured and can be embedded by mobile phone itself. It will have invisible water mark and any size will be easily embedded by the software.